Copper-catalyzed double C–S bond formation for the synthesis of 2-acyldihydrobenzo[b]thiophenes and 2-acylbenzo[b]thiophenes. Issue 74 (13th August 2020) - Sangeetha, Subramani; Sekar, Govindasamy
Abstract : Efficient domino methods are developed for the synthesis of 2, 3-dihydrobenzo[ b ]thiophenes and 2-acylbenzo[ b ]thiophenes from 2-iodoketones using in situ generated iodine from by-product KI with a Cu-catalyst and xanthate. Abstract : An efficient domino process is developed for the synthesis of diversely substituted 2, 3-dihydrobenzo[ b ]thiophenes from 2-iodoketones using a Cu-catalyst and easily available xanthate as a sulfur surrogate in good yields. This domino method has been expanded for the synthesis of 2-acylbenzo[ b ]thiophenes using in situ generated iodine (I2 ) from by-product KI in high yields. Treatment of xanthate with the copper(ii )-catalyst reduced it to a Cu(i )-catalyst, which initiates the catalytic cycle. A possible mechanism has been proposed based on the results from XPS-analysis, an iodine color test and several other control experiments.